Censo fitossociológico, avaliação de métodos amostrais e dispersão de espécies arbóreas em fragmento de mata de cerrado - Scalon Filho, Homero (2014)
Limited information is available on the floristic composition of ecosystem and population surveys are time consuming and expensive, and sampling a considerable alternative. The objective of this work was the completion of the census of five native tree species in the forest area of savanah, and subsequent implementation and evaluation of sampling methods employed in phytosociological surveys. The characteristics of frequency, density and dominance absolutes were estimated and observed the dispersion of juveniles relative to the nearest matrix. An area of 75,000 m2 was previously selected in the Santa Madalena farm, district of Itahum, city of Dourados, MS, Brazil, located at coordinates 22o09'07.57" S and 54o59'55.43" O to 483 m high, and divided into 30 smaller areas of 50 x 50 meters to facilitate the identification, marking, counting, measuring and checking of tree evaluated. Species considered due to the high extraction for presenting therapeutic capabilities, were Anadenanthera falcata (Bth) Speg (angico-preto-do-cerrado), Bauhinia holophyla (Bong.) Stend (falsa-pata-de-vaca), Dimorfanda mollis Benth (faveiro-do-cerrado), Duguetia furfuraceae (St. Hil.) B. et H. (araticum-do-cerrado) and Tabebuia aurea (Manso) B. et H. (para-tudo). Were collected Circumference at Breast Height - CBH, canopy diameter and georeferenced position. The diameter of the canopy was estimated from the average of the largest diameter and the other transverse to it, allowing the estimation of the mean radius, which was then transformed into area pantries to estimate the coverage area CA of each species. The CBH was used for calculation of dominance parameter affect the basal area. The frequency was calculated as the number of individuals observed and the number of areas in which the species occurred, and the density was expressed as number of individuals per unit area (acres). Values of frequency, density and dominances relatives were used to calculate the Importance Value Index - IVI. The data georeferencing were launched in Software AutoCad generated six maps in scale 1:400, being a general map and five, one for each species evaluated. The maps were divided into quadrants for analysis of dispersion and sampling strategies from them were established with variation of the area sampled to evaluate the effectiveness of different sampling systems used in phytosociological surveys in forest savannah. 549 individuals were found with CBH above 0.02 m being the species with the highest number araticum (155 individuals), and falsa-pata-de-vaca the lowest occurrence (9 individuals). The CA was generated by five species of 922.959 m2 ha-1, this being 476.832 m2 ha-1 refers to angico and only 3.289 m2 ha-1 for the falsa-pata-de-vaca. The angico still showed higher dominance (1.212) and IVI (103.560), and falsa-pata-de-vaca only 0.003 of dominance and IVI of 5.22. CBH values were transformed in diameter at breast height - DBH and distributed into five classes in order to investigate their distribution according to age groups, and it was found that the class of younger subjects, there was suppression of the species, indicating strong impacting action and electing distribution in age classes as an important tool for understanding the phenological state of the forest. Treatments faced with the census sampling methods were composed of varying areas. Most methods differ significantly in phytosociological parameters of the sense performed. For the evaluation of the number of individuals para-tudo the method of sample plots was efficient. For estimates the phytosociological parameters any of sampling methods can be recommended for forest savannah, in the conditions that this study was conducted